Le site de la médiathèque Entre Dore et Allier à Lezoux (Puy-de-Dôme) : des traces papillaires antiques en contexte d’atelier de potiers - Aurore Lambert; André Desmarais; Cyril Driard (Gallia)
A Roman settlement specializing in the production of ceramics was discovered during the rescue excavation prior to the construction of the library of Lezoux. Thousands of fingerprints and palm marks belonging to manufacturers who worked in the pottery workshops were discovered there. Such discoveries are not uncommon in archaeological contexts, but studies of them are rare. We studied the best preserved fingerprints on the site, on objects intended for ceramic kiln loading, and defined a recording and survey protocol. Questions about the identification of individuals, age and sex determination were discussed in order to collect as much information as possible about the owners of the traces. The results obtained are positive. However, they could be enhanced with improved techniques. This analysis provided original data about the workforce of the discovered potters’ workshops and enabled us to discuss social aspects, which are rarely documented by other archaeological data.